Effectiveness of allergen-specific immunotherapy with pollen allergens in children from the viewpoint of molecular allergology - S.M. Nedelska; O.D. Kuznietsova (Zaslavsky O.Yu., 2017)
Background. Allergen-specific immunotherapy as elimination procedures is the only method of treatment and prevention of allergic disorders formation and exacerbation of clinical symptoms. One of the approaches to molecular diagnosis is choice of allergen for allergen-specific immunotherapy (ASIT). The purpose of our study was to identify possible reasons of failure of ASIT with pollen allergens (predominantly weeds) in children with seasonal allergic rhinitis (hay fever) and/or bronchial asthma based on studying hypersensitivity to the allergens, analysis of anamnestic data. Materials and methods. Allergy skin prick tests were conducted to 192 children (middle age 9.8 ± 2.7 years) with the seasonal symptoms of rhinitis and/or bronchial asthma according to standard methodology with pollen allergens of Immunolog Ltd (Vinnytsia). We evaluated positive results as 5 mm and higher diameter of papula/hyperemia. The anamnestic survey was carried out in 52 patients by means of the questionnaire that contained questions about cross allergy (pollen-food, oral allergy syndrome), concomitant pathology of upper respiratory tract and effectiveness of АSІТ, which is elaborated by us. Results. The skin prick tests show that in 192 patients, who have hay fever, ragweed, sunflower sensibilization predominates (56 and 58 %, correspondingly). About 10-20 % of children are sensitive to cereals (ryegrass, fescue). To the allergens of poplar, acacia, couch-grass, oak, mint, nettle, walnut, the positive reactions of prick tests were observed in 3-7 children, that is 1.5-3.6 %. According to our results, 23 % of patients had sensibilization to 5 and more pollen allergens. 52 % of children had concomitant food allergy, 15 % of patients have reactions of the lips, oral cavity when using certain products, mostly tomatoes, nuts, seeds (they were diagnosed oral allergy syndrome). Also, one third of children have varying degrees of adenoid hypertrophy, tonsils hypertrophy, allergic rhinitis is complicated by sinusitis in 13 % of cases. Children received 3 to 4 courses of preseason subcutaneous ASIT (December to May) according to classic scheme. The vast majority of children got mixed extracts of ragweed, cyclachaena, mugwort, quinoa, sunflower (90 %). One allergen (ragweed or sunflower) has been used only in 6 children (10 %). We detected that 1/5 children had no clinical effect, the symptoms of hay fever were not diminished or changed their temporal frames. 82 % of patients without effect of ASIT had cross plant-food allergy (oral allergy syndrome). Conclusion. Before the beginning of АSІТ in children with hay fever, the doctor must define a high-risk group in relation to its possible ineffectiveness. We suggest taking into account children with sensitization to 4 and more pollen allergens, with the presence of oral allergic syndrome, concomitant pathology of ENT organs, in particular, adenoid hypertrophy, chronic sinusitis. Such children are recommended to make a profile of molecular allergy diagnostics to determine the specific immunoglobulines Е to the major and minor allergens. Component resolved molecular allergy diagnostics maybe also helpful in estimation the risk of systemic (anaphylactic) reactions in children with cross reactivity (pollen-food allergy) and in improvement of preventive measures, in particular, in patients with oral allergy syndrome.